Numerical investigations on pilot ignited high pressure direct injection natural gas engines: A review. (October 2021) - Li, Menghan; Wu, Hanming; Liu, Xiaori; Wei, Zhangning; Tian, Hongjian; Zhang, Qiang; Li, Zhenguo
Abstract: Pilot ignited high pressure direct injection natural gas engines have a lower tendency of end-wall gas formation owing to the fuel introduction method. Thus, this type of engines are adaptable to high compression ratios and have the potential to achieve low emission levels. In this paper, numerical investigations concerning underexpanded gas jets and in-cylinder working process of pilot ignited high pressure direct injection natural gas engines are involved. The different numerical models adopted in the previous studies are systematically evaluated, giving guidance for the selection of numerical methods during the development of pilot ignited natural gas engines. The results indicate that analytical models could predict jet penetration with high accuracy while Mach disk height and diameter could be well reproduced by empirical correlations. Computational fluid dynamic models could provide more detailed information of jet flow fluid compared to analytical models and empirical correlations. Among all the computational fluid dynamic models, RANS models are considered as the most computational efficient ones while DNS is the most time consuming choice. If only the macro parameters are concerned, RANS models are the best choices. However, if near-field detailed structures are emphasized, using LES models is a better solution. When conducting three-dimensional simulations of the engine working process, RANS models are the most efficient choices for the modeling of in-cylinder flow field while reduced dual fuel mechanism coupled with phenomenological soot models could capture the in-cylinder combustion and emission formation processes with high-precision. Highlights: The analytical models for jet penetration of underexpanded gas jets are summarized. The analytical and empirical models for Mach disk structures of underexpanded gas jets are analyzed. CFD methods for the simulation of underexpanded gas jets are assessed. Turbulence models, kinetic mechanism and soot models used for the simulation of in-cylinder working process are evaluated.